Pengaruh Kompensasi dan Kepemimpinan Terhadap Kinerja Karyawan - Ary Prasetyo; Daris Purba; Suratman Suratman (Jurnal Mirai Management, 2023)
This study aims to determine the direct effect of compensation variables and leadership variables on employee performance variables. The method used in this research is quantitative by using a questionnaire or questionnaire as a research instrument. The data collection technique in this study was to use a simple random sampling technique with a sample of 150 people from a total population of 700 people. The analysis used in this study is the structural equation model (SEM) with Amos version 24 software. The results of this study include the compensation variable (x_1) having a positive but not significant effect on employee performance variable (Y) and the leadership variable (x_2) having a positive and negative effect on employee performance. significant to the variable job satisfaction (Y). The magnitude of the direct influence of compensation variables and leadership variables on employee performance variables is 7.3%. Kata Kunci: Compensation, Leadership, Employee Performance, SEM AMOS.